2020
DOI: 10.1530/eje-20-0415
|View full text |Cite
|
Sign up to set email alerts
|

Progression of vertebral fractures in long-term controlled acromegaly: a 9-year follow-up study

Abstract: Objective Growth hormone (GH) and insulin-like growth factor 1 (IGF-1) excess results in both reversible and irreversible musculoskeletal damage, including increased vertebral fracture (VF) risk. The prevalence of VFs is approximately 60% in controlled acromegaly patients, and these VFs can progress in time. We aimed to identify the course of VFs in a cohort of acromegaly patients in long-term remission and their associated risk factors during prolonged follow-up. Methods Thirty-one patients with acromega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 65 publications
1
21
0
1
Order By: Relevance
“…However, patients with controlled acromegaly can continue to develop VFs. In a 9.1-year prospective follow-up study [29], VFs progressed in 11/31 (35.5%), with patients post-surgery or post-radiation demonstrating a higher risk of VF progression (p = 0.030).…”
Section: What's Newmentioning
confidence: 99%
“…However, patients with controlled acromegaly can continue to develop VFs. In a 9.1-year prospective follow-up study [29], VFs progressed in 11/31 (35.5%), with patients post-surgery or post-radiation demonstrating a higher risk of VF progression (p = 0.030).…”
Section: What's Newmentioning
confidence: 99%
“…A study showed signi cantly higher serum sclerostin levels in active acromegaly patients compared to controls and sclerostin levels correlated with the GH and IGF-1; nevertheless, VFs and bone turnover markers were not evaluated (22). Other limitation is that the study involved only active acromegaly patients although increased prevalence and incidence of fractures in biochemically controlled acromegaly patients was shown in previous studies (9,12,14). İn another study which included active and controlled acromegaly patients, patients with acromegaly had signi cantly lower sclerostin levels than the control group (23).…”
Section: Discussionmentioning
confidence: 96%
“…Hypogonadism is found to be associated with VFs towards acromegaly patients in several studies (7)(8)(9). However, the data were con icted considering the association between hypogonadism and VFs, since no relation was shown in a recent study (14).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, in the studied cohorts of long-term, well-controlled acromegalic patients, the prevalence and progression of VFs was high, showing that the deleterious effects of GH and IGF-1 excess on bone persist despite achievement of longstanding remission. [3][4][5].…”
Section: Introductionmentioning
confidence: 99%